Kriminalisasi Kelalaian dalam Perbuatan Persiapan Tindak Pidana Terorisme di Indonesia - Situmorang, Yoppy Kurniawan (Al-Jinayah : Jurnal Hukum Pidana Islam, 2019)
The research topic follows the absence of law regarding criminal provisions over preparation for criminal terrorism seen as negligence. Based on the issue mentioned, this research is focused on whether conducts due to negligence are punishable by law and on the formulation of regulation over the negligence regarding the preparation to prevent criminal terrorism in Indonesia. This research employed normative legal method along with statute, conceptual, and comparative approaches, while the legal research comprised both primary and secondary materials, both of which were analysed with systematic, grammatical, teleological, and futuristic interpretation.The research learns that 1) conducts seen as negligence in criminal terrorism are still considered as threatening, thus early punishment should be delivered for early prevention. The threat that becomes concern is linked to the network of terrorist organisation although it only begins with negligence. 2) Looking at policy in criminal cases and comparing Indonesia and Australia, the author proposes the following content of Article: anyone who, due to negligence, joins pre-military and military training, or other forms of training linked to terrorist organisations both in the state and overseas, directly and indirectly, and is aware of the situation that his/her act is considered as part of preparation for terrorism, he/she is sentenced to ten-year imprisonment.